On the anisotropic response of a Janus drop in a shearing viscous fluid - Díaz-Maldonado, Misael; Córdova-Figueroa, Ubaldo M. (Journal of fluid mechanics, 2015)
The force and couple that result from the shearing motion of a viscous, unbounded fluid on a Janus drop are the subjects of this investigation. A pair of immiscible, viscous fluids comprise the Janus drop and render it with a ‘perfect’ shape: spherical with a flat, internal interface, in which each constituent fluid is bounded by a hemispherical domain of equal radius. The effect of the arrangement of the internal interface (drop orientation) relative to the unidirectional shear flow is explored within the Stokes regime. Projection of the external flow into a reference frame centred on the drop simplifies the analysis to three cases: (i) a shear flow with a velocity gradient parallel to the internal interface, (ii) a hyperbolic flow, and (iii) two shear flows with a velocity gradient normal to the internal interface. Depending on the viscosity of the internal fluids, the Janus drop behaves as a simple fluid drop or as a solid body with broken fore and aft symmetry. The resultant couple arises from both the straining and swirling motions of the external flow in analogy with bodies of revolution. Owing to the anisotropic resistance of the Janus drop, it is inferred that the drop can migrate lateral to the streamlines of the undisturbed shear flow. The grand resistance matrix and Bretherton constant are reported for a Janus drop with similar internal viscosities.